Effect Size Estimation of Child Stunting Determinants in Surakarta, Central Java - Jemmi Sastrawijayah; Bhisma Murti; Burhannudin Ichsan (Masters Program in Public Health, 2024)
Background: Child growth is one of the public health indicators in monitoring the nutritional and health status of a population. One of the nutritional problems that is of major concern is the prevalence of stunting in toddlers. Stunting is still a problem in the world. This study aims to analyze the reestimation of the magnitude of the determinant effect of stunting on children under five in the city of Surakarta, Central Java.Subjects and Method: This was a cross-sectional study conducted in Pajang and Sibela community health centers (Puskesmas) in Surakarta, Central Java. Total sample of 200 children under five was selected using fixed disease sampling, consisted of 50 stunted children and 150 normal children. The dependent variable was stunting. The independent variables were exclusive breastfeeding, maternal height, maternal history of illness, maternal age at pregnancy, maternal height, and family income. The data were collected using questionnaire and analyzed using a multiple logistic regression.Results: Maternal age ≥20 years (aOR= 0.19; 95% CI= 0.06 to 0.58; p=0.004), maternal height ≥160 cm (aOR= 0.30; 95% CI= 0.12 to 0.74; p= 0.009), and family income high (aOR= 0.29; 95% CI= 0.12 to 0.72; p=0.008) reduces the risk of stunting. Children under five who were not exclusively breastfed (aOR= 27.06; 95% CI= 8.13 to 90.05; p <0.001) and frequent illness in mothers (aOR= 12.69; 95% CI= 4.59 to 35.10; p<0.001) increases the risk of stunting.Conclusion: Maternal age ≥20 years, maternal height ≥160 cm, and family income high reduce the risk of stunting. Children under five who were not exclusively breastfed and frequent illness in mothers increase the risk of stunting. Keywords: stunting, maternal age, maternal height, income, breastfed, illness, children